Design of Experiments for Identifying the Throughput Performance of Shuttle-Based Storage and Retrieval Systems. (2017) - Lerher, Tone
Abstract: This study explores statistically significant factors affecting the performance of new automated storage and retrieval system technology called a Shuttle-Based Storage and Retrieval System (SBS/RS), under pre-defined factors by using Design of Experiment (DOE). After determining the significant factors affecting the SBS/RS performance, a DOE analysis was used to find the design that optimizes a throughput performance of the SBS/RS. The results indicate that five pre-defined factors: number of columns C, velocity of the shuttle carrier v x, acceleration/deceleration of the shuttle carrier a x, velocity of the elevator's lifting table v y, acceleration/deceleration of the elevator's lifting table a y have an interaction effect on each of the performance measures of the studied SBS/RS. The performance measures considered in this study were average single command and dual command cycle times of the shuttle carrier and the elevator's lifting table, average throughput performances and of the shuttle carrier and the elevator's lifting table and the warehouse volume.